Chlorambucil versus observation after anti-Helicobacter therapy in gastric MALT lymphomas: results of the international randomised LY03 trial - Hancock, Barry W (Blackwell Publishing Ltd, 2009)
Gastric mucosa-associated lymphoid tissue (MALT) lymphomas are uncommon tumours characterised by a tendency to remain localised for long periods. The aetiological association between MALT lymphomas and Helicobacter pylori is well established. The role of additional chemotherapy after H. pylori eradication in localised MALT lymphomas is unclear. The LY03 trial was designed to establish whether chlorambucil after treatment for H. pylori would help prevent recurrence. Patients were treated with antibiotics for H. pylori infection. Those with successful eradication of H. pylori and no evidence of progression of lymphoma were eligible for randomisation to chlorambucil or observation. Two hundred and thirty-one patients were registered. Ninety-seven percent patients had H. pylori eradicated after antibiotics and 59% achieved macroscopically normal gastric mucosa. One hundred and ten patients were randomised. With a median follow-up of 58 months, six patients were dead and 17 had recurrent/progressive disease. The recurrence/progression rates at 5 years were 11% for chlorambucil, and 21% for observation with a difference of 10%, 95% confidence interval (CI) = −9% to 29%, P = 0·15. No difference was detected in recurrence/progression-free survival [Hazard Ratio (HR) = 0·96, 95% CI = 0·41–2·2, P = 0·91] or overall survival (HR = 1·93, 95% CI = 0·39–9·58, P = 0·42). This is the first randomised trial to show there is no good evidence to support that additional single agent chemotherapy to anti-H. pylori treatment contributes to prevent recurrence in localised gastric MALT lymphomas.